Highly sensitive non-enzymatic glucose sensing using Ni nanowires and graphene thin film on the gate area of extended gate electric double-layer field-effect transistor - Sheng-Chun Hung (Heliyon)
This study presents an innovative glucose detection platform, featuring a highly sensitive, non-enzymatic glucose sensor. The sensor integrates nickel nanowires and a graphene thin film deposited on the gate region of an extended-gate electric double-layer field-effect transistor (EGEDL-FET). This unique combination of materials and device structure enables superior glucose sensing performance. Ni nanowires were deposited on the surface of the extended gate region of the EGEDL-FET, where high quality monolayer graphene grown by chemical vapor deposition (CVD) had been previously transferred. The Ni nanowires provide a high surface area and excellent catalytic activity for non-enzymatic glucose oxidation. Meanwhile, the graphene thin film enhances the conductivity of the sensing interface due to the matching of work functions between the Ni nanowires and the graphene. The bimetal gate-electrolyte interface with a spacing of 65 μm forms an electric double layer that effectively avoids ion shielding due to its dimension being smaller than the Debye length. This configuration significantly amplifies the electrical signal, thereby enhancing the sensor's sensitivity. The fabricated EGEDL-FET glucose sensor demonstrates a wide linear range from 0.05 mM to 5 mM, high sensitivity of 1043 mA μM−1 cm−2, and a low detection limit of 51 nM. The synergistic effect of the Ni nanowires, graphene film, and EGEDL-FET configuration results in a highly sensitive non-enzymatic glucose sensor with excellent selectivity in glucose alkaline solutions containing both chloride ions and potassium ions. These experimental results represent a promising advancement for glucose monitoring systems, offering improved performance and reliability.